Diagnosis and Treatment of Lower Extremity Peripheral Artery Disease - Novi Kurnianingsih (Universitas Brawijaya, 2021)
Peripheral artery disease (PAD) is a chronic occlusive disease of arteries in the lower extremity due to atherosclerosis. PAD can lead to intermittent claudication, which is weakness or pain with walking alleviated with rest. Until now, the awareness of the public and medical personnel regarding PAD is still not as high as the alertness of coronary disorders. This editorial will focus on diagnosing and treating PAD focused on lower extremity artery disease (LEAD).